Taxonomic and nomenclatural aspects of Hypoxylon taxa from southern South America proposed by Spegazzini - Hladki, Adriana Ines (2009)
The holotypes and isotypes of 20 Hypoxylon taxa described by Spegazzini have been examined and their taxonomic positions and nomenclatural problems are discussed. Two new combinations, Annulohypoxylon apiahynum comb. nov. and A. subeffusum comb. nov., are proposed. H. goliath is considered a synonym of Rosellinia bunodes. H. albostigmatosum and H. guarapiense are synonyms of H. anthochroum, H. anthracoderma of H. monticulosum, H. mbaiense of H. notatum, H. paulistanum of H. diatrypeoides, H. plumbeum and H. rubiginosum var. microcarpum of H. perforatum. H. porteri and H. intermedium belong in Biscogniauxia capnodes, H. puiggarii in Annulophypoxylon subeffusum, H. subvinosum. in H. lenormandii, H. turbinatum var. guaraniticum in Phylacia turbinata and H. valsarioides in Creosphaeria sassafras. H. leptascum is transferred to A. leptascum, H. circostomum to Nemania circostoma and H. latissimum to N. latissima. The holotype of H. albostigmatosum has been recovered, thus the lectotypification by Shear no longer is needed. H. subnigricans and H. umbilicatum are confirmed as good taxa. H. anthochroum and H. lenormandii are reported as first records from Argentina (Tucumán).